The Mystery Of The Fire Dragon - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1961)
where Nancy travels from New York to Hong Kong to find Chi Che Soong, the kidnapped granddaughter of a neighbor. Using a rare fire dragon symbol as a clue, she uncovers an international smuggling ring and rescues Chi Che from a ship
Keywords: roactive, courageous, and highly intelligent investigation, contrasting sharply with the chaotic, illegal actions of the criminal, smugglers; revolves around themes of justice, loyalty, and the courage to confront danger to protect others